The Role of Learning Media in Increasing Students' Learning Interest in Islamic Religious Education Subjects - Taufikurrahman; Mahsur; Sahdan; Halil Hadiatman (Edumaspul: Jurnal Pendidikan, 2026)
The decline in students' interest in learning Islamic Religious Education subjects is one of the challenges in the world of education, especially in today's digital era. The lack of an approach that is relevant to technological developments causes learning Islamic religious education to feel monotonous and less attractive to students. In this study, the researcher wants to aim to discuss and analyze the role of learning media in increasing students' interest in learning in Islamic Religious Education subjects through literature review from various related journals. With the development of technology, it makes it very easy for teachers to convey the material to be taught, then it is also very helpful for students in understanding the material being taught. The use of technology-based learning media is believed to provide a broader, more interesting, effective and efficient learning experience in this day and age. The method used in this study is a qualitative research method with data collection techniques in the form of literature studies, which includes analysis of relevant scientific journals. The results of the study show that the role of learning media is very effective in the process of learning and teaching activities, especially in the subject of Islamic religious education. Media such as educational videos, interactive animations, Islamic podcasts, and online learning platforms are able to create a more interesting, participatory, and appropriate learning atmosphere in accordance with the characteristics of the digital generation. However, in choosing media, teachers must be creative and understanding in choosing the media that will be used to achieve learning goals according to the desired ones. Teachers must also choose easy and cheap learning media that does not burden the teacher himself and the student's parents. In addition, teachers must also be good at using technology-based learning media, such as learning applications, educational videos, and other digital platforms, because they have great potential in increasing students' interest in learning and creating an interactive, flexible, and accessible learning environment, especially in Islamic religious education subjects.